(untitled) (Jurnal Adabiya, 2020)
Peusijuek is one of traditional rituals in the Acehness culture. This tradition is usually done to invoke salvation, peace and happiness in life. As one of the cultural heritages, the peusijuek tradition is rich in values and special meaning. One of them is the use of plants in the ritual of peusijuek, which is used as symbols for hopes and prays. This paper would like to discuss about the types of plants used in the peusijuek tradition so that it can be recognized by the wider community, as to increase knowledge about the cultural traditions of the Acehnese people.